Immune disorders associated with juvenile recurrent chronic parotitis - Antonio David Hidalgo-Santos; Rubén Gastón-Téllez; Begoña Ferrer-Lorente; Raquel Pina-Pérez; Manuel Oltra-Benavent (Anales de Pediatría (English Edition), 2021)
Introduction: Juvenile recurrent chronic parotitis (JRCP) is a rare disease of unknown cause. There is a growing interest in its autoimmune aetiology and its relationship with dysfunctions of cellular and humoral immunity, although there is no agreed protocol for complementary investigations for its study. A consecutive series of cases is presented where the immune alterations and associated autoimmune disorders are investigated, proposing a study algorithm. Patients and methods: A retrospective study was carried out on patients who had JRCP during the period from 2013 to 2016 and a follow-up of at least 2 years. After its clinical and ultrasound diagnosis, complementary examinations were systematically carried out to investigate infectious, immune, and autoimmune diseases. Results: Of a total of 36 patients with inclusion criteria, 16 (44%) were found with some analytical alteration of a non-specific immunological nature (positive ANA, high IgG, low complement factor 4), or associated with a specific diagnosis, as occurred in 11 patients: Selective IgA deficiency (2), Sjögren’s syndrome associated or not with systemic lupus erythematosus (3), coeliac disease associated or not with diabetes mellitus (4), Hashimoto’s thyroiditis (1), and acquired immunodeficiency syndrome (1). Conclusion: Juvenile recurrent chronic parotitis can be considered a sentinel sign of other diseases of immunological/autoimmune aetiology for which the diagnosis, monitoring and early treatment can improve its prognosis. Viral infectious aetiology, with the exception of HIV, is not a priority in the study of recurrences. Resumen: Introducción: La parotiditis crónica recurrente juvenil (PCRJ) es una enfermedad infrecuente de causa desconocida. Existe un creciente interés por su etiología autoinmune y su relación con disfunciones de la inmunidad celular y humoral aunque no existe un protocolo consensuado de investigaciones complementarias para su estudio. Se presenta una serie consecutiva de casos donde se investigan las alteraciones inmunes y trastornos autoinmunes asociados, proponiendo un algoritmo de estudio. Pacientes y métodos: Se realizó un estudio retrospectivo de pacientes que presentaron PCRJ durante el periodo de 2013 a 2016 y seguimiento de al menos 2 años. Tras su diagnóstico clínico y ecográfico se realizaron de forma sistemática exámenes complementarios para investigación de patologías infecciosas, inmunes y autoinmunes asociadas. Resultados: De un total de 36 pacientes con criterios de inclusión, se encontraron 16 (44%) con alguna alteración analítica de carácter inmunológico inespecífico (ANA positivo, IgG elevada, factor 4 del complemento bajo) o asociada a un diagnóstico específico como ocurrió en 11 pacientes: déficit selectivo de IgA (2), síndrome de Sjögren asociado o no a lupus eritematoso sistémico (3), celiaquía asociada o no a Diabetes mellitus (4), tiroiditis de Hashimoto (1) y síndrome de inmunodeficiencia adquirida (1). Conclusión: La parotiditis crónica recurrente juvenile puede considerarse un signo centinela de otras enfermedades de etiología inmunológica/autoinmune cuyo diagnóstico, seguimiento y tratamiento precoz puede mejorar su pronóstico. La etiología infecciosa vírica, exceptuando el VIH, no es prioritaria en el estudio de recurrencias.